Criticality Analysis of Water Catchment Areas in Depok City, West Java - Irsyad Syaifudin; Saptomo, Satyanto K; Pandjaitan, Nora H (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
The rapid development of Depok City has led to a high demand for the construction of facilities for housing and commercial areas. This can result in a decrease in water catchment areas, which can cause water shortages and flooding. The purpose of this study was to identify and create a map of water catchment areas using a geographic information system (GIS) and analyze the infiltration rate and cumulative infiltration in Depok City. The method used was spatial data extraction and spatial analysis of the condition of the water catchment area by scoring potential infiltration and actual infiltration. Spatial analysis was also performed by overlapping spatial data for water catchment area zoning. Infiltration measurement using a double-ring infiltrometer based on SNI 7752:2012. Infiltration rate analysis using the Horton model. The mapping results show that Depok City is dominated by slightly critical criteria, covering an area of 15,589.327 ha (77.98%), followed by conditions that are starting to be critical, covering an area of 4,146.347 ha (20.75%), and natural normal conditions, covering an area of 168,515 ha (0.84%). The highest infiltration rate was measured in Cipayung at 0.330 cm/minute, and the lowest was recorded in Cilodong at a rate of only 0.110 cm/minute. The smallest cumulative infiltration value was 15.744 cm/h, and the largest was 51.886 cm/h.